If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-4(2x-9)+6(-x+1)=8x-5(3x-3)
We move all terms to the left:
-4(2x-9)+6(-x+1)-(8x-5(3x-3))=0
We add all the numbers together, and all the variables
-4(2x-9)+6(-1x+1)-(8x-5(3x-3))=0
We multiply parentheses
-8x-6x-(8x-5(3x-3))+36+6=0
We calculate terms in parentheses: -(8x-5(3x-3)), so:We add all the numbers together, and all the variables
8x-5(3x-3)
We multiply parentheses
8x-15x+15
We add all the numbers together, and all the variables
-7x+15
Back to the equation:
-(-7x+15)
-14x-(-7x+15)+42=0
We get rid of parentheses
-14x+7x-15+42=0
We add all the numbers together, and all the variables
-7x+27=0
We move all terms containing x to the left, all other terms to the right
-7x=-27
x=-27/-7
x=3+6/7
| 2w+-10=2 | | x+3/11=2/3 | | 4.11-2m=2(4–m) | | 24=3/4(x+7) | | 11x55=121 | | 8=w+255 | | /0.25x-12=18-0.55x | | p-65/5=6 | | 3/4m=6.5 | | 1/2(w+2)=5 | | | | | | | | | | | | | | | | | | 2+7y=3-3y | | | | | | | | | | | | | | | | | | | | | | | | | | |